Antibiotic tetracycline enhanced the toxic potential of photo catalytically active P25 titanium dioxide nanoparticles towards freshwater algae Scenedesmus obliquus. (March 2021) - Roy, Barsha; Suresh, P.K.; Chandrasekaran, Natarajan; Mukherjee, Amitava
Abstract: Titanium dioxide nanoparticles (TiO2 NPs) often co-exist with the other co-contaminants like antibiotics. The antibiotics can potentially modify the toxic effects of the co-contaminants like the NPs in the environment. Hence, the present study aims to understand the toxic potential of a binary mixture of tetracycline (TC) and TiO2 NPs to a model freshwater alga – Scenedesmus obliquus . Since, TiO2 NPs are known to be photo-catalytically active, non-irradiated (NI-TiO2 NPs), UVA pre-irradiated (UVA-TiO2 NPs), and UVB pre-irradiated (UVB-TiO2 NPs) TiO2 NPs was mixed separately with TC and their toxicity evaluated. It was observed that the cell viability for the three experimental groups decreased significantly (p < 0.001) with respect to the individual NPs-treated algae. Abbott's model suggested that the interaction between TC and Ni-TiO2 NPs was additive for all the concentrations of NI-TiO2 NPs tested. However, in the case of both the UV pre-irradiated NPs, the interaction was additive for the lower concentration (1.56 μM) and synergistic for both the higher concentrations (3.13, and 6.26 μM). At the concentrations tested the cell membrane damage and intracellular uptake of NPs increased significantly (p < 0.05) for the mixture in comparison with the individual NPs treated algae. This study suggested that even a non-lethal concentration of TC (EC10 = 0.135 μM) increased the toxic potential of the TiO2 NPs significantly and when this antibiotic was used in combination with the UV pre-irradiated NPs, toxicity even increased to a higher level. Highlights: TC interacts synergistically with UV pre-irradiated TiO2 NPs. Though highly toxic, TC did not produce ROS in the freshwater algae. A very low dose of TC also increased the toxic potential of TiO2 NPs in the mixture. TC increased the internalization of TiO2 NPs in S. obliquus .